Design, simulation, and experimental validation of a 50 kg biomass-fired coffee drying oven - Nuramal, Agus; Jaya, Efran Riansyah Rahmat; Suryadi, Dedi; Zuliantoni1, Zuliantoni; Hardiansyah, Hardiansyah; Putra, Rama Dani Eka (Politeknik Negeri Lhokseumawe, 2026)
Despite coffee is one of the leading commodities in Bengkulu Province, the traditional drying process of coffee beans for 10-14 days are still a common practice. This research aims to design, fabricate, and evaluate the thermal performance of a 50 kg capacity wood-fueled coffee drying oven. A three-dimensional CFD model was developed using ANSYS Fluent to analyze temperature distribution within the drying chamber and optimize thermal performance prior to fabrication. Experimental testing was conducted to validate the numerical predictions under controlled operating conditions. The proposed technology is distinguished by its use of locally available biomass fuel. The results of the coffee drying oven simulation, under empty conditions, achieved the desired temperature based. The drying time for coffee beans in this research was 9 hours, achieving a moisture content of 10% to 13% (a moisture content of 12.5% is the Indonesian National Standard. Simulation results predicted chamber temperatures ranging from 67°C to 87°C with an inlet temperature of approximately 100°C, indicating adequate thermal conditions for drying. Experimental measurements showed good agreement with the CFD model, reaching near-steady thermal conditions within 25 minutes.